The frequency of mutations in the penA, mtrR, gyrA and parC genes of Neisseria gonorrhoeae, the presence of tetM gene and antibiotic resistance/susceptibility: a systematic review and meta-analyses - Mendes, Ana Clara; de Souza, Renan Pedra; Bahia, Diana (Frontiers in Microbiology, 2025)
Gonorrhoea is currently one of the most important sexually transmitted infections (STIs) due to the increasing spread of multidrug-resistant strains of N. gonorrhoeae. The aim of this study was to analyse the association between resistance or decreased susceptibility to antibiotics in N. gonorrhoeae and the presence of mutations in the penA, mtrR, gyrA and parC genes, and the presence of tetM gene. We conducted a systematic review according to the PRISMA guidelines. We selected 19 studies for the penA gene, 23 for gyrA and parC, 18 for mtrR and 12 for tetM using the Science Direct and PubMed databases. Meta-analyses of isolates resistant to penicillin, cefixime and ceftriaxone showed that more than 50% of isolates had mutations in the penA and mtrR genes. More than 50% of azithromycin-resistant isolates had mutations in the mtrR gene, while more than 50% of ciprofloxacin-resistant and intermediate-resistant isolates had mutations in gyrA. Less than 50% of the isolates with intermediate resistance to ciprofloxacin had mutations in parC. The plasmid containing the tetM gene was found in more than 50% of tetracycline-resistant isolates. Infection surveillance and genetic studies are important for controlling the spread of the disease, which can improve the quality of life of infected people and reduce the financial burden on public health systems.